2020
DOI: 10.1111/ajad.12999
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Korsakoff's Syndrome for Inhibition but Not for Episodic Memory or Flexibility

Abstract: Background and Objectives While sex differences in cognitive abilities have been extensively studied in healthy populations, little is known about these differences in patients with Korsakoff syndrome (KS). Methods We investigated sex differences in verbal episodic memory, inhibition, and flexibility in 25 patients with KS and 25 control participants. Results The analysis demonstrated no significant differences between women with KS and men with KS on episodic memory and flexibility, but higher inhibition was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Earlier research by El Haj et al also found evidence of sex differences between males and females diagnosed with KS. In their study, female patients showed a better inhibition behavior than males [38]. It would be of interest to investigate sex differences between people with KS in larger samples.…”
Section: Discussionmentioning
confidence: 89%
“…Earlier research by El Haj et al also found evidence of sex differences between males and females diagnosed with KS. In their study, female patients showed a better inhibition behavior than males [38]. It would be of interest to investigate sex differences between people with KS in larger samples.…”
Section: Discussionmentioning
confidence: 89%
“…In patients with AUD, the severity of memory deficits is similar between men and women [ 71 ]. Regarding patients with KS, a recent study reported no gender effect on episodic memory performance [ 72 ]. Although we cannot assess this potential bias in our study, which constitutes a limitation, the studies reported above suggest that the observed group difference in episodic memory is unlikely to be attributed to a gender effect.…”
Section: Discussionmentioning
confidence: 99%